2011
DOI: 10.1158/1078-0432.ccr-11-0166
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-494 Downregulates KIT and Inhibits Gastrointestinal Stromal Tumor Cell Proliferation

Abstract: Purpose: Gain-of-function mutations and KIT overexpression are well-known tumorigenesis mechanisms in gastrointestinal stromal tumors (GIST). This study aimed to discover microRNAs (miRNA) that target KIT and reveal the relationship between the discovered miRNAs and KIT expression in GISTs.Experimental Design: Fresh-frozen GISTs from 31 patients were used to confirm the relationship between miR-494 and KIT expression using quantitative reverse transcription-PCR to assess miR-494 expression levels and Western b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 34 publications
3
81
0
1
Order By: Relevance
“…We identified several miRNAs down-regulated after the PED S104G overexpression and, among these, we focused on miR-494 because it exhibited the highest fold change. MiR-494 is known as an oncomir in gastrointestinal stromal tumors targeting the proto-oncogene KIT (28). In addition, miR-494 enhances myocyte survival by targeting PTEN, ROCK1, and CAMKIId and protects against ischemia/reperfusion-induced cardiac injury (29).…”
Section: Discussionmentioning
confidence: 99%
“…We identified several miRNAs down-regulated after the PED S104G overexpression and, among these, we focused on miR-494 because it exhibited the highest fold change. MiR-494 is known as an oncomir in gastrointestinal stromal tumors targeting the proto-oncogene KIT (28). In addition, miR-494 enhances myocyte survival by targeting PTEN, ROCK1, and CAMKIId and protects against ischemia/reperfusion-induced cardiac injury (29).…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, miR-494 has been reported to promote cancer cell death. 10,21 These findings suggest that miR-494 exhibits differential effects on divergent targets to balance a common signaling pathway and eventually, determine the expression phenotype. Regardless, miR-494 is abundantly expressed in a variety of organs, such as the brain, heart, liver, and kidneys ( Figure 2).…”
Section: Discussionmentioning
confidence: 97%
“…9 As for the physiologic functions of miR-494, almost all focus has been on cancer research. 10,11 In the heart, experiments with transgenic mice overexpressing cardiac-specific miR-494 showed that elevation of miR-494 improved the post-I/R recovery of cardiac function and suppressed I/R-triggered cardiomyocyte apoptosis and necrosis. 8 However, whether miR-494 plays an important role in the regulation of renal I/R injury is unknown.…”
mentioning
confidence: 99%
“…Furthermore, Romano et al (2012) found that miR-494 was regulated by ERK1/2 and modulated by tumor necrosis factorrelated apoptosis-inducing ligand-induced apoptosis in non-small-cell lung cancer through BIM downregulation. The findings by Kim et al (2011) indicated that miR-494 was a negative regulator of KIT in gastrointestinal stromal tumors (GISTs), and overexpressing miR-494 in GISTs might be a promising approach to GIST treatment. Previously, Li et al found that downregulation of miR-494 via the loss of SMAD4 increased FOXM1 and β-catenin signaling in pancreatic cancer cells.…”
Section: Discussionmentioning
confidence: 99%